MELANOMA DIŞI DERİ KANSERLERİNİN NÜKS ORANLARI: 11 YILLIK RETROSPEKTİF ANALİZ - ÜLKÜR, Ersin; KARAGÖZ, Hüseyin; AÇIKEL, Cengiz; YÜKSEL, Fuat; ÇELİKÖZ, Bahattin (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Surgical excision of basal cell and squamous cell carcinoma includes a margin of healthy skin, because the microscopic margin is often considered to extend beyond the macroscopic margin. According to our general clinical principals, we excise the majority of basal cell carcinomas with a 3-5 mm, and squamous cell carcinomas with 4-6 mm margin of skin that appears clinically healthy with local anesthesia. Results.- This retrospective study of 516 patients treated surgically for primary nonmelanotic skin cancer was conducted from January 1994 to January 2005 and frequency of recurrence was defined. The sum of the patients with basal cell carcinoma was 378 (73.2%), and squomous cell carcinoma was 138 (26.8%). The number of the recurrence was 33 with basal cell carcinoma and 10 with squamous cell carcinoma. All of the recurrent basal cell carcinomas and the 8 (80%) of recurrent squamous cell carcinomas were at the head and neck region. The frequency of recurrence is higher than the literature. Conclusion.- Results of this study suggest that reduced excision margins anyway increased recurrence rate of tumor.